Розроблення та обґрунтування антикризової стратегії діяльності підприємства - Михайленко, Ольга Валеріївна; Майстренко, Альона Василівна (My University, 2019)
У статті представлено комплексний підхід до формування антикризової стратегії підприємства, що включає у себе повний аналіз стану підприємства, фінансового стану споживачів, а також наявності проблем в економіці країни та світовій економіці. Актуальність даної теми полягає не тільки у розробленні конкретних етапів антикризової стратегії управління підприємством, а й у доцільності застосування антикризової стратегії на тій чи іншій фазі розвитку того ж підприємства. Основна мета статті – правильне застосування конкретних антикризових мір на підприємстві, порівняння антикризового управління з довгостроковим управлінням підприємством, а також основні етапи формування антикризової стратегії. Проблема формування системи антикризового управління є надважливою для підприємств, оскільки бізнес-процеси прискорюються, що вимагає від підприємств мати стратегії для виживання в складних економічних умовах та забезпечити своє успішне існування в майбутньому. In this article presents the development of a strategy of anti-crisis management of an enterprise for its future profitable activity. The relevance of this topic lies not only in the development of specific stages of the anti-crisis strategy of enterprise management, but also in the expediency of applying the anti-crisis strategy at a particular phase of development of the same enterprise. It is also important to understand the difference between long-term company management and anti-crisis man-agement of this company. This difference significantly affects the existence of the company in a crisis situation. The main purpose of the article is the correct application of specific anti-crisis measures at the enterprise, comparison of anti-crisis management with long-term management of the enterprise, as well as the main stages of the formation of an anti-crisis strategy. The results of the study showed that it is important to establish the causes of the crisis and its diagnosis, it is necessary to take into account the implementation period, as well as factors of the internal and external environment, the specifics of the sale of goods and services, and the life cycle stage. At each stage of the life cycle of an enterprise, anti-crisis measures should be different and aimed at solving specific problems. For each phase of the life cycle, an anti-crisis strategy and the necessary measures for its implementation are presented. The anti-crisis strategy is a comprehensive analytical model of the enterprise in conditions of dynamic changes in the internal and external environment in all phases of the life cycle, aimed at achieving the ultimate goal - long-term economic sustainability and financial stability of the enterprise, with the possibility of further development of the company. The problem of creating an effective anti-crisis management system is extremely important for enterprises, since business processes are accelerating, and global markets are becoming increasingly unstable, which requires enterprises to have in their arsenal means and strategies for surviving in difficult economic conditions and ensuring their future success.
Keywords: криза; управління підприємством; crisis; anti-crisis management; кафедра обліку і аудиту